Optimization of row and hill spacing patterns improved rice population structure and increased rice yield - Dong, Liqiang; Yang, Tiexin; Ma, Liang; Li, Yuedong (Frontiers in Plant Science, 2025)
ObjectiveThe objective of this study was to investigate the effects of row and hill spacing patterns on rice populations during mechanized production, material accumulation and transport, and photosynthetic characteristics and to explore the role of these factors in improving rice yield.MethodsAn field experiment was conducted from 2022 to 2023 with Liaojing 419 as the test material under four planting modes: LFM: local farmer cultivation mode was used as a control; and CDM: conventional densification mode; NDM: narrow row densification mode; and WNDM: wide narrow row densification mode were used as the treatment modes. Field mechanized transplantation experiments were conducted to investigate the effects of plant pattern on the physiological and morphological characteristics of rice plant individuals and populations, and clarify the relationships of physiological and biochemical changes with row and hill spacing.ResultsThe result shows that WNDM presented the greatest yield advantage in the two years trial, with yield significantly greater than that of the local farmer mode and other densification modes, with an increase of more than 8% compared with LFM. The reciprocal second leaf yielded the highest values, at 27.33 μmol·m-2·s-1 and 27.13 μmol·m-2·s-1under the WNDM over two years, which were significantly higher than those of the other modes. The WNDM resulted in the greatest accumulation of biomass during the heading–maturity stage, with values of 6.23 t/ha and 6.07 t/ha, respectively. Compared with the LFM, the WNDM had higher biomass at maturity, at 23.64 t/ha and 23.75 t/ha for two years, an increase of 17.90% and 17.87%, respectively. The sugar spikelets ratio was highest under the WNDM, which was significantly greater than those in the CDM and NDM.ConclusionsThe wide narrow row densification mode of mechanized transplanting not only improved yield but also effectively optimized the population spatial distribution, improved resource utilization efficiency, and presented high production adaptability and promotion potential.SignificanceThis study provides theoretical and practical references for improving rice production efficiency and promoting high-quality mechanized processes in Northeast China, which is highly important for achieving sustainable development in modern agriculture.